Employment and Job Satisfaction Of Agricultural Communications Graduates - Blannie E. Bowen; Barbara E. Cooper (Journal of Applied Communications, 1988)
Few studies have focused upon the occupational structure of agricultural communications or the job satisfaction of agricultural communications professionals. This void in the literature prompts questions about the types of positions falling under the broad umbrella of agricultural communications. For teaching faculty, in agricultural communications, a more specific question is frequently posed: What types of positions do majors in agricultural communications pursue after graduation, and how satisfied are the graduates with their positions? The primary purpose of this study was to determine the types of positions held by Ohio State University agricultural communications graduates. A second purpose was to assess their salaries and level of job satisfaction. A mailed questionnaire was sent to 131 agricultural communications alumni. The response rate was 57.1 %. The graduates held a variety of positions in agricultural communications and most were satisfied with their positions. Their annual salaries depended upon the type of position held, age, and gender. The best indicators of job satisfaction were ACT membership and annual salaries which the graduates earned.